Correction: Progressive multifocal leukoencephalopathy during 4 years of Palbociclib for advanced breast cancer with a history of follicular lymphoma patient - Mariko Nishihara; Ryosuke Koyamada; Tetsuhiro Masaki; Tomohito Shimada; Kazuhiro Ishikawa; Jun Hashimoto; Nobuyoshi Mori; Asami Namai; Hideaki Yokoo; Kenta Takahashi; Tadaki Suzuki; Kazuo Nakamichi; et al. (Journal of NeuroVirology, 2025)

Progressive multifocal leukoencephalopathy during 4 years of Palbociclib for advanced breast cancer with a history of follicular lymphoma patient - Ryosuke Koyamada; Mariko Nishihara; Tetsuhiro Masaki; Tomohito Shimada; Kazuhiro Ishikawa; Jun Hashimoto; Nobuyoshi Mori; Asami Namai; Hideaki Yokoo; Kenta Takahashi; Tadaki Suzuki; Kazuo Nakamichi; et al. (Journal of NeuroVirology, 2025)
A 67-year-old woman with a history of follicular lymphoma and recurrent breast cancer with multiple metastasis developed PML during receiving fluvestrant plus palbociclib. Rituximab and bendamustine had finished 6.5 years ago. Discontinuing palbociclib and using mirtazapine, she is alive a year after diagnosis of PML. It is rare for PML to be diagnosed long after the last dose of rituximab and bendamustine. We will discuss the possible involvement of palbociclib in the course of PML.

Two new triterpenoids from the leaves and stems of Lantana camara - Masateru Ono; Asami Hashimoto; Mayu Miyajima; Aimi Sakata; Chisato Furusawa; Mizuki Shimode; Shuhei Tsutsumi; Shin Yasuda; Masafumi Okawa; Junei Kinjo; Hitoshi Yoshimitsu; Toshihiro Nohara (Natural Product Research, 2021)